Incubator type affects human blastocyst formation and embryo metabolism: a randomized controlled trial. Issue 12 (26th October 2022) - Kermack, Alexandra J; Fesenko, Irina; Christensen, David R; Parry, Kate L; Lowen, Philippa; Wellstead, Susan J; Harris, Scott F; Calder, Philip C; Macklon, Nicholas S; Houghton, Franchesca D
Abstract: STUDY QUESTION: Does the type of incubator used to culture human preimplantation embryos affect development to the blastocyst stage and alter amino acid utilization of embryos in assisted reproduction? SUMMARY ANSWER: Culturing embryos in a time lapse system (TLS) was associated with a higher Day 5 blastocyst formation rate and altered amino acid utilization when measured from Day 3 to Day 5 compared to the standard benchtop incubator. WHAT IS KNOWN ALREADY: Culture environment is known to be important for the developing preimplantation embryo. TLSs provide a stable milieu allowing embryos to be monitored in situ, whereas embryos cultured in standard benchtop incubators experience environmental fluctuations when removed for morphological assessment. STUDY DESIGN, SIZE, DURATION: A prospective clinical trial randomizing 585 sibling embryos to either the TLS (289 embryos) or the standard benchtop incubator (296 embryos) over a 23-month period in a UK University Hospital Fertility Clinic. PARTICIPANTS/MATERIALS, SETTING, METHODS: Participants were aged 42 years or under, had an antral follicle count of ≥12 and ≥6 2 pronucleate zygotes. Zygotes were cultured individually in 25 µl of medium. Randomized embryos were graded and selected for transfer or cryopreservation on Day 5. For those embryos produced by women who underwent stimulation with recombinant FSH injections and were triggered with hCG, spent medium was collected on Day 5 for amino acid analysis by high pressure liquid chromatography. Clinical pregnancy was defined as the presence of a foetal heart beat on ultrasound scan at 7 weeks. MAIN RESULTS AND THE ROLE OF CHANCE: Overall, blastocyst formation rate on Day 5 was significantly higher in embryos cultured in the TLS (55%) compared to the standard incubator (45%; P  = 0.013). Similarly, there was an increase in the number of blastocysts suitable for cryopreservation in the TLS (31%) compared to the standard incubator (23%; P  = 0.032). There was a significant difference in the utilization of 12 amino acids by blastocysts cultured from Day 3 to Day 5 in the TLS compared to the standard incubator. Embryos cultured in the TLS displayed an increased total amino acid utilization ( P  < 0.001) and reduced amino acid production ( P  < 0.001) compared to those in the standard incubator. Irrespective of incubator used, embryos fertilized by ICSI depleted significantly more amino acids from the medium compared to those fertilized by conventional IVF. There was no difference in the mean score of blastocysts transferred, or the clinical pregnancy rate after transfer of embryos from either of the incubators. LIMITATIONS, REASONS FOR CAUTION: The study was not powered to discern significant effects on clinical outcomes. WIDER IMPLICATIONS OF THE FINDINGS: The metabolism and development of preimplantation embryos is impacted by the type of incubator used for culture. Further research is required to investigate the long-term implications of these findings. STUDY FUNDING/COMPETING INTEREST(S): NIHR Southampton Biomedical Research Centre Commercial and Enterprise Incubator Fund funded this study. The TLS was provided on loan for the study by Vitrolife. The authors declare no conflict of interests. TRIAL REGISTRATION NUMBER: ISRCTN73037149 TRIAL REGISTRATION DATE: 12 January 2012 DATE OF FIRST PATIENT'S ENROLMENT: 21 January 2012